The Socio-Religious Perspectives of Cremation in Yorubaland - Ogunbiyi, David Oluwabukunmi; Oluwasanmi, Olusola; Alabi, Godwin Fortunatus; Adedibu, Babatunde Aderemi (Corpus Intellectual, 2024)
Cremation is a funeral method that uses extreme heat to reduce the human body to its fundamental parts. Recently, people have started cremating the corpses of their loved ones, yet the issue of cremation is a trending but controversial topic in Yorubaland, especially in Lagos, Nigeria, as there are lots of cultural and religious issues surrounding it. Therefore, this research focuses on the religious perspectives of cremation in Yorubaland. It also examined cremation from philosophical, Islamic, Biblical, and African sociological perspectives in Yorubaland, with little or no references to other tribes in Nigeria or Africa. This research adopted a descriptive sampling methodology with 280 respondents from two main religious organisations and several ethnic groups in Lagos State, and the data were analysed and discussed. It discovers that most of the Christian denominations in Yorubaland do not have a specific official statement that either endorses or condemns cremation, hence leaving the choice to individuals and families. Islamic scholars also believe that cremation is forbidden by God in the Quran and that the only acceptable manner of disposing of a dead body is Islamic burial. The study reveals that, in the religious and ethnical context, cremation faces huge opposition, with traditional burial being the most preferred method of body disposal in Yorubaland.